A pilot study of umbilical cord‐derived mesenchymal stem cell transfusion in patients with primary biliary cirrhosis. (15th July 2013) - Wang, Lifeng; Li, Jin; Liu, Honghong; Li, Yuanyuan; Fu, Junliang; Sun, Ying; Xu, Ruonan; Lin, Hu; Wang, Siyu; Lv, Sa; Chen, Liming; Zou, Zhengsheng; et al.
Abstract: Background and Aim: Ursodeoxycholic acid (UDCA) treatment is an effective medical therapy for patients with primary biliary cirrhosis (PBC); however, 40% of PBC patients show an incomplete response to the UDCA therapy. This study aimed to investigate the safety and efficacy of umbilical cord‐derived mesenchymal stem cell (UC‐MSC) transfusion in PBC patients with an incomplete response to UDCA. Methods: We conducted a single‐arm trial that included seven PBC patients with a suboptimal response to UDCA treatment. UC‐MSCs were first cultured, and then 0.5 × 10 6 cells/kg body weights were infused through a peripheral vein. UC‐MSCs were given three times at 4‐week intervals, and patients were followed up for 48 weeks. Primary outcomes were to evaluate the safety and feasibility of UC‐MSC treatment, and secondary outcomes were to evaluate liver functions and patient's quality of life. Results: No obvious side‐effects were found in the patients treated with UC‐MSCs. Symptoms such as fatigue and pruritus were obviously alleviated in most patients after UC‐MSC treatment. There was a significant decrease in serum alkaline phosphatase and γ‐glutamyltransferase levels at the end of the follow‐up period as compared with baseline. No significant changes were observed in serum alanine aminotransferase, aspartate aminotransferase, total bilirubin, albumin, prothrombin time activity, international normalized ratio, or immunoglobulin M levels. The Mayo risk score, a prognostic index, was also stable during the treatment and follow‐up period. Conclusions: UC‐MSC transfusion is feasible and well tolerated in patients with PBC who respond only partially to UDCA treatment, thus representing a novel therapeutic approach for patients in this subgroup. A larger, randomized controlled cohort study is warranted to confirm the clinical efficacy of UC‐MSC transfusion.